Energy dissipation during disintegration of red-bed soft rock in the Shengzhou-Xinchang area of Zhejiang Province, China - Shenggen HUANG; Mingjian HE (地质科技通报, 2024)
Objective This study focused on the surface energy characteristics of red-bed soft rocks during disintegration in the Shengzhou-Xinchang area of Zhejiang Province. Methods Based on the principle of energy dissipation, this study analyzed the conversion, transfer, and dissipation of energy during the process of disintegration under dry-wet cycles for three groups of red-bed soft rocks, considering different compositions in the study area. This study aimed to explore the law of energy absorption and transformation into surface energy during the process of red-bed soft rock disintegration. Results The results show that the surface energy accumulation of the red-bed soft rock in the study area undergoes three stages with an increasing number of dry-wet cycles: a slow growth stage, a rapid growth stage, and a stable stage. The results also indicate that the higher the content of clay minerals in the red-bed soft rock is, the more surface energy it generates, and the poorer its resistance to disintegration. Conclusion The energy dissipation model proposed in this study provides a reference for the governance of various failure problems of the red-bed soft rock in the Shengzhou-Xinchang area of Zhejiang Province.